Participatory Leadership Behavior, Achievement Orientation, and Work Motivation Have a Significant Effect on Teacher - Rosnawati, Rosnawati; Latif, Mukhtar; Anwar, Kasful; Jamaluddin, Jamaluddin (CV. Zabags Qu Publish, 2023)
This research aims to reveal the influence of participatory leadership behavior, performance orientation on job satisfaction mediated by work motivation. In order to the target of the buyer, the quantitative research method used to design a route analysis with a sample of 106 respondents originating from MTSN 1 Batam, MtsN 2 Natuna, Tanjung Pinang in Riau Islands Province. The data collection method used is an angket that is subsequently in the process of statistical analysis. The results of this study show that Participatory Leadership Behavior, Performance Orientation has a direct and simultaneous effect on job satisfaction. Participatory leadership behavior and performance orientation have a direct influence on job motivation. More than 50% of participatory leaders' behavior directly affects Job satisfaction through Job Motivation. The novelty in study was the role of participatory leadership behavior found to have a greater influence on job satisfaction than previous research.